THE IMPLEMENTATION OF MARKETING COMMUNICATION IN ATTRACTING PROSPECTIVE STUDENTS INTEREST TO STUDY AT VOCATIONAL HIGH SCHOOL - Daradjat, dkk, Ridwan Setiawan; Hafiar, Hanny (Prodi Teknologi Pendidikan, 2015)
Abstract, Research is entitled